PENGARUH DOSIS PEMUPUKAN PADA SISTEM TANAM TUMPANGSARI TERHADAP PERTUMBUHAN DAN HASIL JAGUNG MANIS DAN KEDELAI - Okti Herliana; Atang .; Isnan Ujiono (Jurnal Agroekoteknologi, 2015)
This research aimed to determine growth pattern and production of crops grown with mono and multiple cropping systems and to calculate Land Equivalency Ratio (LER). The research was conducted at the experimental field of Faculty of Agriculture of Jenderal Soedirman University, from March toMay 2015. The variables observed for corns were plant height, leaf number, corncob, corncob length, while for soybean were plant height, leaf number, weight and number of pods pods, as well as LER. This study used a randomized block design (RBD) with two factors, i.e cropping systems (M1: Mono cropping, M2: Mltiple cropping) and fertilizers (P0: 0 % doses fertilizer, P1: 50% doses fertilizer and P3: 100% doses fertilizer). The data were analyzed using analysis of variance (F test) and if significantly different were tested further by a further test LSD (Least Significant Difference) at 5% error level. These results indicated that the mono and multiple cropping had significantly affected on plant height and leaf number but did not significantly affect on corncob, corncob length. Similarly, in plant height, leaf number, weight and number of pods of soybean pods is no different. LER value for each trial was > 1.Keywords: corn, soybeans, LER, monocropping, multiple cropping